2004
DOI: 10.1016/j.virol.2004.09.014
|View full text |Cite
|
Sign up to set email alerts
|

An attenuated West Nile prototype virus is highly immunogenic and protects against the deadly NY99 strain: a candidate for live WN vaccine development

Abstract: In a short time, West Nile virus has developed into a nationwide health and veterinary problem. The high virulence of the circulating virus and related lineage 1 WN strains hinders development of an attenuated live vaccine. We describe an attenuated WN isolate, WN1415, which is a molecularly cloned descendant of the WN prototype B956 strain. The parent virus belongs to lineage 2, members of which have not been associated with epidemic or epizootic outbreaks. A set of non-conservative mutations, mostly in non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…All 7 isolates from 2004 were from Arizona and had 2 common silent mutations in env: 1320 A → G present in all isolates, and 1974 C → T, present in 6 of 7 isolates. Mutation 1320 A → G is also present in reported attenuated strains of WNV (AY532665, AY688948, M12294) (29) and was also reported in human isolate DQ164201 from Arizona in 2004 and in the red-tailed hawk isolate DQ164204 from Colorado in 2003 (18). Mutation 1974 C → T, found in isolates from Arizona and Texas, was detected in 2000 in New York (AF404756), which indicated that this mutation occurred at least twice.…”
Section: Resultsmentioning
confidence: 73%
“…All 7 isolates from 2004 were from Arizona and had 2 common silent mutations in env: 1320 A → G present in all isolates, and 1974 C → T, present in 6 of 7 isolates. Mutation 1320 A → G is also present in reported attenuated strains of WNV (AY532665, AY688948, M12294) (29) and was also reported in human isolate DQ164201 from Arizona in 2004 and in the red-tailed hawk isolate DQ164204 from Colorado in 2003 (18). Mutation 1974 C → T, found in isolates from Arizona and Texas, was detected in 2000 in New York (AF404756), which indicated that this mutation occurred at least twice.…”
Section: Resultsmentioning
confidence: 73%
“…However, in some of these studies, mice immunized with recombinant protein succumbed to high dose WNV challenge, suggesting that the efficacy of subunit vaccination may be limited by a failure to stimulate CD8 + T cell immunity. Live-attenuated WNV vaccines derived by serial passage have also been evaluated: vaccination with an attenuated Israeli isolate protected mice and geese from lethal challenge with a virulent WNV stain [27,28]. A plasmid expressing the fulllength genome of an attenuated Kunjin strain of WNV was also protective in mice [29].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations leading to loss of envelope (E) protein glycosylation together with mutations in the nonstructural (NS) protein genes may be associated with attenuation of these viruses (6). Comparisons between the prototype Uganda strain (B956) and a variant of this strain, which was obtained by molecular mutation (B956D117B3), showed changes in the E and NS genes, which resulted in reduced virulence in mice (7). These attenuations could not, however, be correlated with clinical disease in humans because these strain were either isolated from birds or modifi ed in culture.…”
mentioning
confidence: 99%